MODELING THE IMPACT OF ECOSYSTEM SERVICES ON LIFE CYCLE ASSESSMENT USING THE END POINT. - PASLAVSKYI, MYKHAILO; RUDA, MARIA; DZHUMELIA, ELVIRA; SOKOLOV, SERGII; PASLAVSKYI, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The characterization coefficients and framework developed in this paper describe the relative contribution of the effects of land-use occupation and land-use change (as an inventory flow entity) to ecosystem service damage measured in biophysical units. Generalized performance factors and frameworks are based on the relationship of these new average impact categories to the three traditional protection zones of human health, the natural environment (often referred to as «ecosystem quality») and natural resources. This intermediate approach adds more «noise» to existing life cycle assessment methodology protocols, potentially reducing the ease of interpretation by decision makers. An endpoint-based approach, while involving trade-offs around increased data requirements for practitioners, will provide easier understanding for decision makers. This paper proposes an approach to include net changes in ecosystem service supply as endpoint impacts in the new three protection zones in life cycle assessment. This proposal is based on the literature reviewed, which examines the potential for incorporating ecosystem services into life cycle assessment methodologies, and attempts to address some of the limitations of existing approaches. Modeling the impact of a wind power plant on the supply of ecosystem services in the life cycle assessment methodology should take into account both the use of the supply of ecosystem services for the assimilation of emissions, and the change in the supply of ecosystem services due to stress and/or transformation of the spatio-temporal geosystem. The approach presented here provides a platform for doing so.Although the proposed conceptual framework is ready for application, there are some challenges. They address which ecosystem service to include, how to weigh different ecosystem services and impacts, and building a database of ecosystem service impacts for background processes. The proposed framework requires more data and research to develop a spatio-temporal geosystem ecosystem service-specific characteristic factor to convert life cycle inventory results into a common unit of impact category indicators, but can build on existing natural capital and ecosystem service assessment modeling tools and data to do so.